2016
DOI: 10.1037/ccp0000117
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mindfulness-based addiction treatment (MBAT) for smoking cessation and lapse recovery: A randomized clinical trial.

Abstract: Objective To compare the efficacy of Mindfulness-Based Addiction Treatment (MBAT) to a Cognitive Behavioral Treatment (CBT) that matched MBAT on treatment contact time, and a Usual Care (UC) condition that comprised brief individual counseling. Method Participants (N=412) were 48.2% African-American, 41.5% non-Latino White, 5.4% Latino and 4.9% other, and 57.6% reported a total annual household income < $30,000. The majority of participants were female (54.9%). Mean cigarettes per day was 19.9 (SD= 10.1). Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 84 publications
3
105
0
8
Order By: Relevance
“…For these patients, optimal treatment may require longer duration treatment or adjunctive behavioral treatments that target smoking behavior in the context of psychological distress. 12,13 Third, APPs may be more likely than physicians to be able to link behaviors that cluster together to enhance readiness to quit smoking. For example, strategies for stress, weight, and fatigue management include healthy eating and walking and other forms of exercise, all of which dovetail into M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 treatment strategies for COPD and smoking cessation.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…For these patients, optimal treatment may require longer duration treatment or adjunctive behavioral treatments that target smoking behavior in the context of psychological distress. 12,13 Third, APPs may be more likely than physicians to be able to link behaviors that cluster together to enhance readiness to quit smoking. For example, strategies for stress, weight, and fatigue management include healthy eating and walking and other forms of exercise, all of which dovetail into M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 treatment strategies for COPD and smoking cessation.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…These differences introduce multiple potential biases related to financial ability, medical literacy, time flexibility, understanding of treatments and make a fair comparison between MTS and WTQL interventions impossible. For a comparison between MTS and various controls (including WTQL), please see randomized trials already conducted on these interventions (Brewer et al, 2011; Davis, Goldberg, et al, 2014; Davis, Manley, et al, 2014; Davis et al, 2013; Vidrine et al, 2016). This trial provides a different perspective through its naturalistic design with more robust ecological validity.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, Mindfulness Training for Smokers (MTS) and similar interventions have been evaluated in a number of randomized controlled trials (RCTs) (Brewer et al, 2011; Davis, Goldberg, et al, 2014; Davis et al, 2014; Davis et al, 2013; Vidrine et al, 2016). A recent meta-analysis across multiple RCTs showed that abstinence rates for MTS were almost twice that of matched behavioral controls (RR = 1.88 (95% CI: 1.04–3.40)) (Oikonomou, Arvanitis, & Sokolove, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness practices, which are centered on teaching awareness and nonreactivity toward craving states, are especially relevant in the treatment of addictive behaviors [42]. Patients practice and learn specific interventions such as breath meditation, mindful eating, and urge surfing, a mindfulness practice applied specifically to cravings [42,43]. In one study, patients who were randomized to mindfulness training for tobacco cessation achieved abstinence rates of 31% at the 17-week follow-up, compared to only 6% of those in the American Lung Association's Freedom from Smoking program [44].…”
Section: Treating the Biopsychosocial Aspects Of Tobacco Use And Addimentioning
confidence: 99%
“…Mindfulness practices teach patients to take a nonjudgmental, nonreactive stance toward present-moment experiences [41]. Mindfulness practices, which are centered on teaching awareness and nonreactivity toward craving states, are especially relevant in the treatment of addictive behaviors [42]. Patients practice and learn specific interventions such as breath meditation, mindful eating, and urge surfing, a mindfulness practice applied specifically to cravings [42,43].…”
Section: Treating the Biopsychosocial Aspects Of Tobacco Use And Addimentioning
confidence: 99%